Cognitive impairment patterns in schizophrenia and affective disorder. Issue 7 (July 1987) - Taylor, M A; Abrams, R
Abstract : A battery of neuropsychological tasks was used to study 62 schizophrenics, 67 melancholics, and 30 manics satisfying specific research diagnostic criteria, and 42 normal subjects. Two patterns of neuropsychological impairment among patients were identified by factor analysis. The first pattern of bifrontal, non-dominant hemisphere dysfunction was shared by schizophrenics and affectively ill patients, whereas the second pattern of dominant temporo-parietal-occipital impairment was most frequent in a subgroup of schizophrenics. These relationships remained after accounting for the effects of age, gender, handedness and drugs received at time of testing.